Effect of hypoxia and high glucose on sodium channels in dorsal root ganglia neurons - Hoai, Ton Thi Bich; Mai, Hoang Van; Thieu, Phan Xuan (Academia Journal of Biology, 2012)
Hypoxia and hyperglycemia are considered as the leading causative factors of diabetes and frequently associated with several complications. Voltage-gated sodium channels are large trans-membrane proteins that contribute to the initiation and propagation of neuronal excitability associated with pain. Here we show that hypoxic and high glucose cellular environment increases the excitability of DRG neurons by increasing amplitude and decreasing duration of action potentials. Na conductance of TTX-S sodium channels increased under the experimental condition that induces the Na gates close and open faster, without affecting the level of genes expression. These data indicate that TTX-S Na current is modulated under hypoxic and high glucose conditions, which might be relevant for diabetes-related complications or other diseases associated with acute hypoxia and hyperglicemia.